2018
DOI: 10.1155/2018/5378502
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences and Experiences in Hyperemesis Gravidarum Treatment: A Qualitative Study

Abstract: Introduction Hyperemesis gravidarum (HG) medical therapies are currently of limited effect, which creates a larger role for patient preferences in the way HG care is arranged. This is the first study using in-depth interviews to investigate patients' preferences and experiences of HG treatment. Materials and Methods We conducted individual in-depth interviews among women who had been hospitalized for HG in North Holland at least once in the past 4 years. We asked them about their experiences, preferences, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…Such findings have been previously limited to anecdotal reports 15 . Similarly, while women’s feelings of not being taken seriously or the trivialisation of symptoms is a common finding in qualitative studies, 8,9 information on the nature of those interactions, in terms of types of medication and healthcare professionals involved, has not previously been explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings have been previously limited to anecdotal reports 15 . Similarly, while women’s feelings of not being taken seriously or the trivialisation of symptoms is a common finding in qualitative studies, 8,9 information on the nature of those interactions, in terms of types of medication and healthcare professionals involved, has not previously been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Despite guidelines recognising the importance of early identification and treatment of NVP/HG, previous studies have shown that women with NVP often report experiencing not being taken seriously by healthcare professionals when seeking treatment 8,9 . This is coupled by evidence of high levels of maternal anxiety, 10 or a reluctance among some health care professionals, 11,12 about the use of medications to treat severe NVP or HG.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the aim of this study the following three tools were used for data collection: Tool I: Structured interview schedule for nurses and women: It was developed by the researcher after reviewing recent related literature [13,14] to collect basic data from nurses and women. (15) and Jasline (2019) (16) and was used by the researcher to collect nurses′ knowledge before, immediately and three months after implementation of the educational program.…”
Section: Tools Of Data Collectionmentioning
confidence: 99%
“…-Low level of knowledge <60% = (0 -14 marks). Tool II: An observational checklist for nurses′ practice: It was developed by the researcher after reviewing recent related literature (14,17,18) to assess nurses′ practice before, immediately and three months after implementation of the educational program regarding hyperemesis gravidarum. It included three items and their subitems related to assessment, intervention and educational roles of the nurse as follow: -Done correctly and completely was scored as (2).…”
Section: Tools Of Data Collectionmentioning
confidence: 99%
“… 13 Women affected by HG report not being taken seriously by caregivers, pressure for them to eat, lack of early intervention to prevent dehydration and the importance of a single room in the hospital to avoid stimuli that evoked vomiting, like light, noise and smells, in particular food, but also body odour and perfumes. 14 Taste and smell capability are impaired in HG, with smell more affected, 15 but how the impairments may impact food and drink tolerances is not known.…”
Section: Introductionmentioning
confidence: 99%